Cofibrations and Bicofibrations for C*-Algebras - Pop, Ioan; Tofan, Alina (Revista Matemática Complutense, 2008)
The paper deals with the correlated concepts of cofibration and bicofibration in C -algebra theory. We study cofibrations of C -algebras introduced by Claude Schochet in [9] (see also [7]). Cofibrations are characterized by means of the mapping cylinder C -algebras. We also define and analyse the notion of bicofi bration for C -algebras based on the topological model from [8] (see also [5]). As an application, an exact sequence of Cerin’s homotopy groups [1] is obtained.